ANALISIS EKONOMI PADA KAWASAN KONSERVASI EKS-SITU TAMAN HEWAN PEMATANG SIANTAR - Johanna Philip Siagian; Muhdi Muhdi; Kansih Sri Hartini (Program studi Kehutanan USU, 2016)
Ex-situ conservation is the preservation of plant species and wildlife are carried out outside the habitat. Animal park Pematangsiantar is one of conservation organizations in North Sumatra, which is engaged in the utilization of fauna to maintain the continuity of existing species therein. This study aimed to: (1) analyze the economic value of conservation areas Animal Park Pematangsiantar (THPS) based on the travel cost method, (2) analyzing the intensity of the visit in THPS, (3) analyze the factors that affect the intensity of visits to THPS. The samples used in this study was 100 respondents, while the sampling technique used was purposive sampling. Based on the result of the analysis carried out that the quantity of the economic value of conservation areas THPS with travel cost method was Rp41.534.982.240,-/year. THPS is the intensity of visits to as many as three visits, whereas the factors that affect the intensity of the visit is the length of journey. Keywords: ex-situ conservation, Pematangsiantar Animal Park, economic value, travel cost method, visitation intensity